Application of Activity-Based Learning Model to Improve Motivation in Learning Aqidah and Ahlak on The Material of The Characteristics of God in Class VII Students of MTs Miftahul Ulum Kareteng - Yuliani; Triwahyunin, Yuyun; Zahra; Kurniawati, Yuyun (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to analyze the application of activity-based learning models in improving students' learning motivation in the subject of Aqidah Akhlaq, especially in the material of the attributes of Allah in class VII MTs. Miftahul Ulum Kareteng. The background of this study is the low motivation of students to understand the concept of the attributes of Allah, which is caused by conventional learning methods that do not actively involve students. Therefore, the activity-based learning model is applied to improve student participation and understanding of the material being taught. The research method used is classroom action research (CAR) which consists of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, learning motivation questionnaires, and learning outcome tests. The subjects of this study were 30 students of class VII MTs. Miftahul Ulum Kareteng. The results of the study showed that the application of the activity-based learning model can significantly increase students' learning motivation. This can be seen from the increasing involvement of students in the learning process, their increasing curiosity about the material being studied, and the increasing learning outcomes of students after the application of this method. In addition, students are more active in discussions, group work, and practical activities designed to strengthen their understanding of the attributes of Allah. In conclusion, the activity-based learning model can be an effective alternative in improving students' motivation and learning outcomes in the subject of Aqidah Akhlaq. Teachers are advised to apply this method continuously to create a more interesting and interactive learning atmosphere.